The Effect of Limitation on Smartphone Use in SDIT Al Madinah - Andina Nurul Wahidah; Syarifah Qutratun Nada (Universitas Tanjungpura, 2019)
Addiction to gadgets in children is one of the main concerns of the government in Indonesia today. Children belonging to the Alfa generation (born in 2010 and above) are also called digital native communities who have been born face to face with the digital world that has so developed. The application of the rules on limiting the use of smartphone should continue to be promoted since the elementary school level. The method used in this research is qualitative with the type of case study research. The study was conducted in the Al Madinah Integrated Islamic Elementary School (SDIT), which is located on Jalan Danau Sentarum, Pontianak Kota District, Pontianak City, West Kalimantan in the 2019/2020 school year. The selection of research subjects using purposive sampling techniques. Data collection techniques through interviews and documentation using semi-structured interview guidelines and supporting documents according to research needs. In-depth interviews were conducted with 3 (three) speakers. Data analysis techniques collected through various techniques and instruments used were analyzed descriptively using the Miles and Huberman models. The impact caused by the implementation of the rules for limiting the use of smartphone at SDIT Al Madinah tends to have a very dominant positive effect, namely (1) increasing the productivity of students' time while at school, and (2) increasing the learning activities of students in the classroom. It greatly affects the learning process in the classroom, and students appear to be more active when there is discussion and make the learning atmosphere better.